Key performance indicators in Tour de France sailing - Philippe, K.; Paillard, T.; Dubois, R.; Maurelli, O.; Prioux, J. (Journal of Sports Sciences, 2021)
This study aimed to determine the key performance indicators of inshore sailing during the sailing Tour de France. Technical and physical parameters were investigated to determine the discriminating factors between successful and less successful international level sailors. Measurements from 21 sailors (mean ± SD; age = 23.81 ± 4.18 years) were conducted prior to the sailing Tour de France. Global Positioning System data of all participating teams (n = 23) was analysed. Sailors were divided into two groups (i.e. successful and less successful) according to qualifying performance percentage. The differences between successful and less successful sailors were explored by means of independent t-tests. Results indicate that successful boats displayed higher maximal speed, higher average speed and more efficient starting performance per race than less successful boats. Successful sailors have stronger handgrip strength, higher isometric maximal voluntary force relative to bodyweight (isometric mid-thigh pull) and more powerful submaximal pulling (bench pull) actions than their less successful counterparts. The results of this study suggest that multiple sailing, physical and physiological variables are related to sailing performance in inshore sailing. Therefore, we emphasize the importance of integrating specific testing protocols to evaluate the performance potential of inshore sailors participating in the sailing Tour de France.